Epidemiology, clinical features and transmission of re-emerging arboviral infection chikungunya - Balamurugan Shanmugaraj; Ashwini Malla; Sathishkumar Ramalingam (Asian Pacific Journal of Tropical Biomedicine, 2019)
A number of re-emerging and emerging infectious diseases including chikungunya, West Nile, yellow fever, Zika, dengue, Japanese encephalitis, and others have increased in recent years, which threaten the public health across the globe. Chikungunya is a neglected re-emerging arboviral infection caused by chikungunya virus. Arboviral infections such as chikungunya, Zika and dengue have similar epidemiology, transmission cycles and clinical symptoms, which makes it difficult to diagnose these three infections. Moreover, there is no commercial vaccine or licensed therapy available for chikungunya infection, thus causing severe burden worldwide. Vector control may reduce the disease risk; however, this remains a challenge due to many factors including, but not limited to, evolution of insecticide resistance in mosquitoes, gaps in vector control tools, urbanization, environmental and demographic changes. Effective integrated vector control strategies and surveillance measures along with affordable vaccine development or anti-viral therapy are essential to control the infection. In this review, we discuss the epidemiology of mosquito-borne infection chikungunya which has re-emerged as an international concern in recent decades.